Pengembangan Organisasi Pemuda dan Olahraga cabang Wushu unit Jatinangor menjadi Organisasi Berprestasi yang Berwawasan Kesehatan dan Kewirausahaan - Muhammad Nur Abdillah; Eva Kusumahati; Anas Bunyamin (Universitas Mathla'ul Anwar Banten, 2020)
DEVELOPMENT OF YOUTH AND SPORTS ORGANIZATIONS OF JATINANGOR’S WUSHU BRANCH INTO ACHIEVEMENT ORGANIZATIONS WITH HEALTH AND ENTREPRENEURSHIP INSIGHT. Youth organization (Karang Taruna) located in Margamulya RT 02 RW 10 Jatinangor developed into a health-oriented youth organization in the field of sports, namely the Jatinangor Wushu Unit (Martial Arts Organization). Events and programs are carried out through sports & health as well as entrepreneurship approaches. A newly established organization with limited access to information and knowledge about the organization, health, and entrepreneurship to achieve outstanding organizations, assisted and facilitated by the STFB Community Service team in collaboration with Padjadjaran University to achieve access to information related to health such as understanding and knowledge about healthy lifestyle pattern, nutrition intake supporting optimal body performance, body anatomy, disease prevention, and others, to support sports achievements, as well as coaching, by providing workshops on health & sports, organizational management also provides assistance in activating the formation of business units by utilizing potential local resources through the design thinking approach. Facilitation activities carried out in 3 main programs: A. Health Improvement Program: 1) Improvement of health knowledge and fitness conditions by training health vital signs and counseling the proper drug’s consumption, accompanied by assessments and monitoring of fitness programs through; 2) Health and Fitness Test; 3) Individual Health Counseling; B. Improvement of Organizational Achievement for Wushu athletes cadre: 4) Counseling of Organization and Leadership; 5) Enhancement of Entrepreneurial Insights, by assisting the activation of business units/entrepreneurs with design thinking approaches: 6) Organizational Business Model Workshops. Based on health and fitness tests, the fitness parameters of prospective wushu athletes must always be measured and mixed in a fitness improvement program through individual health counseling.